Studies of Al-Ti alloys by SEM - Yildiz, K.; Atici, Y.; Keşlio?lu, K.; Vaşar, E. (My University, 2007)
Al-Ti (1, 2 wt. %) alloys were investigated by Scanning Electron Microscopy (SEM). SEM observations and energy-dispersive x-ray analyses (EDX) showed that the phase structure of Al-Ti (1 %) alloy at 165 ?m/s is composed of Al matrix and C, Ni, Fe and Si particles and the Al-Ti (1 %) alloys at 16 and 8 ?m/s have only the Al matrix and C particles, It was also found that the Al-Ti (2 %) form the Al matrix and intermetallic TiAl. © 2007 American Institute of Physics.
6TH International Conference of the Balkan Physical Union -- 22 August 2006 through 26 August 2007 -- Istanbul
Keywords: Al-Ti alloys; EDX; SEM